Phasic Firing of Single Neurons in the Rat Nucleus Accumbens Correlated with the Timing of Intravenous Cocaine Self-Administration - Peoples, Laura L. (J Neurosci, 1996)
To examine potential neural mechanisms involved in cocaine self-administration, the activity of single neurons in the nucleus accumbens of rats was recorded during intravenous cocaine self-administration. Lever pressing was reinforced according to a fixed-ratio 1 schedule. On a time base comparable to the interinfusion interval, half the neurons exhibited phasic firing patterns time locked to the cocaine reinforced lever press. For almost all neurons, this pattern consisted of a change in firing rate postpress, typically a decrease, followed by a reversal of that change. The postpress change was closely related to the lever press. Typically, it began within the first 0.2 min postpress and culminated within the first 1.0 min postpress. For a small portion of responsive neurons, the reversal of the postpress change was punctate and occurred within 1–3 min of either the last lever press or the next lever press so that firing was stable during much of the interinfusion interval. For the majority of neurons, the reversal was progressive; it began within 2 min after the previous lever press, and it was not complete until the last 0.1–2.0 min before the next lever press. The duration of this progressive reversal, but not of the postpress change, was positively correlated with the interinfusion interval. Thus, in addition to exhibiting changes in firing related to the occurrence of self-infusion, the majority of neurons also exhibited progressive changes in firing related to the spacing of infusions. In a structure that has been shown to be necessary for cocaine self-administration, such a firing pattern is a likely neurophysiological component of the mechanism that transduces declining drug levels into increased drug-related appetitive behavior. It is, thus, a neural mechanism that may contribute to compulsive drug-maintained drug taking.